2018
DOI: 10.1021/acs.jmedchem.8b01594
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of N-(4-(6-Acetamidopyrimidin-4-yloxy)phenyl)-2-(2-(trifluoromethyl)phenyl)acetamide (CHMFL-FLT3-335) as a Potent FMS-like Tyrosine Kinase 3 Internal Tandem Duplication (FLT3-ITD) Mutant Selective Inhibitor for Acute Myeloid Leukemia

Abstract: Most of the current FMS-like tyrosine kinase 3 (FLT3) inhibitors lack selectivity between FLT3 kinase and cKIT kinase as well as the FLT3 wt and internal tandem duplication (ITD) mutants. We report a new compound 27, which displays GI50 values of 30–80 nM against different ITD mutants and achieves selectivity over both FLT3 wt (8-fold) and cKIT kinase in the transformed BaF3 cells (>300-fold). 27 potently inhibits the proliferation of the FLT3-ITD-positive acute myeloid leukemia cancer lines through suppressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 42 publications
0
20
0
Order By: Relevance
“…Both compounds 7d and 7b (data in Supplementary material) showed an excellent selectivity profile, having almost no activity on other kinases including FMS and cKit. High selectivity over cKit might be an opportunity to avoid myelosuppression toxicity, which was reported from a dual FLT3/cKit inhibitor [19][20][21][22] . It is a valuable result to secure such a kinase selectivity profile considering the similarities of the same type III receptor tyrosine kinase (FMS, cKit and FLT3).…”
Section: Resultsmentioning
confidence: 99%
“…Both compounds 7d and 7b (data in Supplementary material) showed an excellent selectivity profile, having almost no activity on other kinases including FMS and cKit. High selectivity over cKit might be an opportunity to avoid myelosuppression toxicity, which was reported from a dual FLT3/cKit inhibitor [19][20][21][22] . It is a valuable result to secure such a kinase selectivity profile considering the similarities of the same type III receptor tyrosine kinase (FMS, cKit and FLT3).…”
Section: Resultsmentioning
confidence: 99%
“…This case provided a good model for individualized accurate treatment under the direction of drug sensitivity screening. Even though the ex-vivo approach may not always work as expected as the pharmacodynamics of each patient contribute to the drug sensitivity and toxicity, it did help guide the treatment of many disease, such as chronic myeloid leukemia (CML) (30), acute myeloid leukemia (AML) (31,32) and ALL (33).…”
Section: Discussionmentioning
confidence: 99%
“… 150 We and others have shown that low-passage patient-derived primary cells established from acute myeloid leukemia patients, chronic myeloid leukemia (CML) patients, gastrointestinal stromal tumor (GIST) patients, and sarcoma patients can be used for screening and identifying novel kinase inhibitors in preclinical studies. 151 , 152 Lee et al tested the therapeutic landscape of 60 molecule-targeted compounds on 462 PDCs across 14 cancer types and identified lineage-specific drug associations, such as gastric cancers and PI3K inhibitors. 153 Brodin et al evaluated the sensitivity of 525 anticancer agents on patient-derived sarcoma cells and found that the drug sensitivity of the patient sarcoma cells in vitro correlated with the response of the patient to the treatment received.…”
Section: Advances In Efficacy Assessment Models and Technologymentioning
confidence: 99%